Mobile Bagging System sebagai Solusi Pengemasan Hasil Pertanian: Bachtera Indarto, Didiek Basuki Rahmat, Hasto Sunarno, Andika Yulianto - Bachtera Indarto, Bachtera Indarto; Didiek Basuki Rachmad, Didiek Basuki Rachmad; Hasto Sunarno, Hasto Sunarno; Andika Yulianto, Andika Yulianto (Jurnal Fisika dan Aplikasinya, 2025)
A research on application of mass sensors as a means for packaging agricultural produces has been done. The study was conducted by making the mechanical framework of the packaging tools by weighing indicator as controller of the mass sensor. Mass sensor which used is a rod-type load cell with a maximum capacity of 20 kg. From the data was obtained the amount of packing materials for each different test. 2 kg pack of rice is able to package a total of 17 packs / min, soybean and corn can produce 10 packing / min and 8 packs / min. For 3 kg package, rice capable to package 13 packs / minutes, soybeans 8 packs / min and corn 6 packs / min.